HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN NASABAH BANK SYARIAH NIAGA MADANI DI MAKASSAR - Dirwan Dirga Saputra (AkMen JURNAL ILMIAH, 2011)
The research aim to analyzed the correlation of service quality based on interaction, physical environment and result qualities toward the satisfaction with customer on Syariah Niaga Madani Bank at Makassar and to analyzed between the service quality have strong correlation toward the satisfaction with customer on Syariah Niaga Madani Bank at Makassar. The result of research applied on Syariah Niaga Madani Bank at Makassar, with population of customer as amount 2.264 per December 2010. Sample used of Stratified Proporsional Random Sampling based on Solvin formulation obtained 96 respondents. The method analysis used of Chi-Square, Coefficient Contingence (C) dan Coefficient Contingence Maximal (Cmaks) to see of significant correlation, strong correlation for each variables. The result of research showed that there are correlation of service quality consist of interaction, physical environment and result qualities toward satisfaction, suitable with application of attitude, behavior and expert for interaction in give of satisfaction. Ambient condition, design and social for physical environment toward satisfaction, and result quality such as the time of wait, physical evidence and valence on Syariah Niaga Madani Bank at Makassar. Between service quality it the result of quality have strong correlation toward satisfaction with customer on Syariah Niaga Madani Bank at Makassar, which indication that the satisfaction with customer appointment of the result quality which give from the staff on Syariah Niaga Madani Bank at Makassar.